2019
DOI: 10.1177/1010428319846803
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells targeting PI3K/AKT pathway in leukemic model

Abstract: Mesenchymal stem cells have therapeutic properties that are related to their potentials for trans-differentiation, immunomodulation, anti-inflammatory, inhibitory effect on tumor proliferation, and induction of apoptosis. This study was performed to analyze the role of mesenchymal stem cells as an alternative for cellular signaling growth factors involved in the pathogenesis of leukemogenesis in rats. Treatment of rats with 7,12-dimethyl benz [a] anthracene induced leukemogenesis appeared as a significant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The close correlation between mesenchymal stem cells treatment and downregulation of a PI3K/AKT pathway raises the suggestion of their anti-tumorigenic effect, these suggestions were supported by the work of authors who explained the anti-tumorigenic role of MScs in acute myeloid leukaemia (AML) animal model by their inhibitory effect on PI3K/AKT/mTOR pathway plays, that plays a vital role in the cell survival, proliferation, migration, cell cycle and apoptosis. Furthermore MScs might exert a potential improvement in microenvironment, cytokines in addition to improving proliferation by downregulation of (X-linked inhibitor of apoptosis protein),thus up-regulation BCL2 and P53 in the present study after MSCs treatment further add to the potential ameliorative effect in pulmonary parenchyma [33] .…”
Section: Discussionmentioning
confidence: 62%
“…The close correlation between mesenchymal stem cells treatment and downregulation of a PI3K/AKT pathway raises the suggestion of their anti-tumorigenic effect, these suggestions were supported by the work of authors who explained the anti-tumorigenic role of MScs in acute myeloid leukaemia (AML) animal model by their inhibitory effect on PI3K/AKT/mTOR pathway plays, that plays a vital role in the cell survival, proliferation, migration, cell cycle and apoptosis. Furthermore MScs might exert a potential improvement in microenvironment, cytokines in addition to improving proliferation by downregulation of (X-linked inhibitor of apoptosis protein),thus up-regulation BCL2 and P53 in the present study after MSCs treatment further add to the potential ameliorative effect in pulmonary parenchyma [33] .…”
Section: Discussionmentioning
confidence: 62%
“…MSCs have been shown to produce and release growth factors, exosomes, and cytokines that affect cells in their vicinity, which are induced into different developmental pathways [30]. It has been reported that MSC-derived PI3K/AKT signaling, and lead to protection against oxidative stress-triggered cell death [32]. Therefore, we reasoned that MSCs might target some specific genes or signaling networks to function as a potential therapeutic approach for vitiligo.…”
Section: Mscs Downregulate Pten Expression In Melanocytes In Vitromentioning
confidence: 99%
“…Melanocytes extracted from human foreskin tissue (passed on to the second or third generation) transfected with a PTEN expression plasmid and co-cultured with human BMMSCs resulted in the BMMSCs down-regulating their PTEN expression ( Zhu et al, 2020 ). In addition, BMMSCs can reduce PTEN expression in the presence of oxidative stress in vitro in a 7,12-dimethylbenz [a]anthracene (DMBA)-induced leukemia cell model and a melanocytic vitiligo model, where they increased AKT phosphorylation and prevented oxidative stress-triggered cell death ( Ahmed et al, 2019 ; Zhu et al, 2020 ). Phosphorylation inactivates PTEN ( Vazquez et al, 2001 ; Das et al, 2003 ).…”
Section: Mechanism Of Antioxidant Action Of Mscs and Research Progres...mentioning
confidence: 99%